PROSES PENCIPTAAN MANUSIA SEBAGAI MEDIA PEMBELAJARAN DALAM AL-QURAN - Eliyah Eliyah (Cross-border, 2018)
The media offered by the Koran are very ordinary and understandable and can be easily found by every rational and normal human being. The claims of modern scientists on the truth of the Koran and the truth of the delivery of the Prophet make it easy for them to solve problems that they do not understand is a clear picture of the scientific analysis process in the Koran. This Scientific Analysis is in dire need of the learning experience that has been expressed by Edgar Dale. It is clear that the Koran is the best medium of education for mankind.